KONSEP BUDAYA TOLERANSI DAN PERDAMAIAN DALAM MEWUJUDKAN PERDAMAIAN DUNIA - Ikhwanuddin Al Rosyid, Muhammad; Riyadi, Sugeng; Hamdan; Sigit Al Fajar, Galih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the concept of a culture of tolerance and peace from an Islamic perspective through the Rahmatan lil 'Alamin approach and its relevance in realizing world peace. This study departs from the thoughts of Shaykh Al-Zaytun, who emphasized that religion essentially aims to bring happiness, peace, and harmony to all humanity without distinction of religious, cultural, or national background. The study uses a qualitative approach with a descriptive-analytical library research method. Data sources were obtained from religious texts, historical documents such as the Medina Charter and the Preamble to the 1945 Constitution, as well as various scientific literature relevant to peace education, cultural diplomacy, and interfaith dialogue. Data analysis was conducted through the content analysis method with the stages of data reduction, thematic classification, interpretation, and drawing conclusions. The results of the study indicate that a culture of tolerance is the main foundation in building sustainable peace at the national and international levels. Peace education based on Rahmatan lil 'Alamin values ​​has proven to play a strategic role in shaping the character of an inclusive, moderate, and diversity-respecting society. The implementation of tolerance values ​​through educational institutions, particularly Islamic boarding schools (pesantren), can serve as an instrument of social transformation by instilling a dialogical and non-violent attitude. Furthermore, cultural diplomacy and interfaith dialogue serve as forms of soft power in international relations, encouraging global cooperation without conflict. The values ​​of Pancasila and the principles of the Medina Charter demonstrate the harmony between Islamic teachings and modern constitutions in creating a peaceful pluralistic society. Therefore, the integration of Rahmatan lil 'Alamin (blessing for the universe) values ​​into education, social policy, and international relations is a crucial strategy for realizing a just and sustainable world peace.